Pengurangan Waste dengan Pendekatan Lean Six Sigma - Haniful Athhar (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
An effective and efficient order fulfillment system is absolutely needed to achieve customer satisfaction. However, wastes which occur in production process would hamper toward its progress, that it is necessary to do an efficiency effort by implementing a concept of Lean Six Sigma which is a combination of lean method and six sigma method. Lean method improves process flow and reduce wastes meanwhile six sigma method improve process capability and reduce variations. In measure phase, known that the most significant waste in production process of sugar at PT. PG. Krebet Baru were waiting, Inventory and Defect.Based on that fact, this research was very necessary to be executed to understand the causes of wastes and to make an improvement plan by using Lean Six sigma approach and Analysis of Ishikawa diagram. From analze phase, it is known that the causes of wastes were (a) The split of job description in inspection session is not focus,(b) The filter in chycling mchinedidn't work well caused by unslilled operators, ( c) the number of crushing machine is insufficient so there were material piles. The purposed improvement plans are are (a) Review and improve job description especially in inspection and weighing section, (b) Give additional training to operator who work in spinning section, (c) Machines and tool inspection before starting the production process so it is going to work well.